PRODUCTION OF GREEN DETTOL AS BACTERIAL INHIBITOR AND DISINFECTANT - Muntaha M. Hadi; Majid Rasheed Majeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The aim of this research is production of disinfection (Dettol) contains herbal formula and study the efficacy of it for inhibition of pathogenic bacteria as and comparing with traditional Dettol efficacy. In this research, a herbal disinfectant and antiseptic was prepared similarly to the industrial Dettol and in terms of composition, except for the active substance (chloroxylenol), which was replaced by a plant extract (thyme) and active compound (thymol) separately. total of 50 samples hand swabs were collected randomly from children and housewives and student at university of Baghdad. The following species were isolated from swabs and identified by microscopic morphology, morphological features on culture media, and Vital Index of Traditional Environmental Knowledge(VITEK2)System and that were Staphylococcus aureus, Escherichia.coli, Bacillus cereus ,pseudomonas aeruginosa, Enterobacter cloacae.  The results of study showed that the highest antimicrobial activity was belonged to thymol. while a lowest antibacterial effect was belonged to thyme. Highest value of minimum inhibitor concentration (mic) was (0.09) of thymol against staphylococcus aureus while a lowest mic value was (6.25) of thyme against Bacillus cereus the result of minimum bactericidal concertation (mbc) showed that thymol and Dettol were the same value (1.56) against Enterobacter cloacae.